Indonesia - Sukma, Isrotul; Setiawan, Fajar; Martati, Badruli (Widyagogik, 2025)
This study aims to describe teachers' perceptions of the independent training feature on the Merdeka Belajar (PMM) Platform as an effort to strengthen teacher competence in the context of implementing the Merdeka Curriculum. This research is important to find out the extent to which independent training can support the development of teacher competencies, especially in facing the challenges of curriculum changes based on independence and flexibility. The method used in this research is a descriptive approach with data collection techniques through interviews with teachers in several schools. The data collected was analysed qualitatively to obtain in-depth findings regarding teachers' perceptions of the self-training feature. The results showed that the majority of teachers have a positive perception of the self-training feature in PMM, considering it as a good tool to strengthen professional competencies, especially in technology-based teaching and a more flexible curriculum. However, there are some challenges such as limited time, resources, and access to technology that need to be considered. The conclusion of this study is that the self-training feature in PMM has great potential to support the development of teachers' competencies, but further support is needed from the school and government to make it more effective to overcome the existing obstacles, so that the use of this feature can be optimized in the implementation of the Merdeka Curriculum.